2020
DOI: 10.18231/j.aprd.2020.014
|View full text |Cite
|
Sign up to set email alerts
|

Denture base reinforcing materials - A review

Abstract: Poly methyl methacrylate (PMMA) is one of the most widely used materials for fabricating dentures.Though it has its success in meeting esthetic requirements, it is still far from ideal to meet mechanical requirements of a denture. The fracturing of dentures can be caused by mechanical properties of acrylic resin or by a multitude of factors leading to failure of PMMA. The quest for an alternative material or a chemical modification or use of different denture base material reinforcements of PMMA, provides a cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…This material possesses many advantages such as low cost, ease in fabrication, polishing, biocompatibility, satisfactory aesthetics, low density, and colour matching ability [1,8,9]. In contrast, the associated disadvantages, which include insufficient hardness, flexural strength, toughness, and elastic modulus, make this material highly prone to fracture and cause clinical failure [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…This material possesses many advantages such as low cost, ease in fabrication, polishing, biocompatibility, satisfactory aesthetics, low density, and colour matching ability [1,8,9]. In contrast, the associated disadvantages, which include insufficient hardness, flexural strength, toughness, and elastic modulus, make this material highly prone to fracture and cause clinical failure [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…According to the fact that fiber reinforcement leads to enhance the strength of polymer matrix [12]. Jawad K. investigated the qualities of PMMA reinforced with Siwak fibers and found that the tensile properties improved.…”
Section: Introductionmentioning
confidence: 99%
“…Statistically ANOVA and Bonferroni tests showed significant differences among the groups [17]. Also, different type of nanotube were utilized to improve the dental material properties such as; Carbon nanotubes (CNTs), TiO2 nanotubes, ZrO2 nanotubes and halloysite nanotubes (HNT) Copper nanotube CNTs used due to the advance properties; CNTs specially used because it considered strong, resilient, and lightweight [12,18].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the conventional heat-polymerized polymethyl methacrylate [PMMA] denture base material fractured when loaded under flexural or impact strengths that exceeded its flexural or toughness capacity (1,6) . The insufficient flexural strength, flexural modulus, and toughness are determinable for the clinical success of the conventional acrylic denture base (7,8) . So, various clinical and in vitro attempts were made to overcome these mechanical drawbacks (6,7) .…”
Section: Introductionmentioning
confidence: 99%